SYNTHESIS THIN LAYER ZnO-TiO2 PHOTOCATALYSTS SOL GEL METHOD BY USING THE PEG (Polyethylene Glycol) AS SOLVENT - Tanti Haryati; Novita Andarini; Mellisa Ika Febrianti (Jurnal ILMU DASAR, 2012)
The incorporation of TiO and ZnO material as a composite, to increase the activity of the catalyst. Synthesis of ZnO-TiO2 thin layer made using a sol-gel method with a variation of PEG as a solvent. The purpose of this research was to investigate the structure and morphology of ZnO-TiO2 thin layer on the variation of PEG as a solvent by sol-gel method . Preparation of ZnO sol of the precursor , while the TiO2 sol synthesized by dissolving the anatase TiO2 structure into polyethilen glycol . Sol of ZnO and TiO2 sol do sol mixing to form ZnO–TiO2 after it coated on a glass substrate and then calcined . Products were then characterized by X-ray diffraction to determine the crystal structure and SEM to determine its morphology . The test results show the crystal structure by XRD based difaktogram intensity , the greater the molecular weight of the PEG peak intensity of ZnO-TiO2 showed the lower. While based on morphological examination , it can be seen that the larger molecular weight PEG , ZnO - TiO2 granular greater.